EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL), NUMBERED HEAD TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) TERHADAP PRESTASI BELAJAR DITINJAU DARI KREATIVITAS BELAJAR SISWA PADA MATERI HIMPUNAN SMP NEGERI KABUPATEN KEBUMEN - Putri, Prihastini Oktasari; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of this research are to know: (1) which one was better result in learning achievement of mathematics among PBL, NHT, and TPS, (2) which one was better learning achievement among students in high, middle, and low creativity categories of Â mathematics, (3) in each learning model, which one was better learning achievement among studentsâ creativity categories, students having high, middle, or low; and (4) in each creativity categories, which one was better learning achivement among students of PBL, NHT, or TPS. This research used quasi-experimental research. The population was all of the students in Grade VII of State Junior High School in Kebumen. The samples of research were taken by using stratified cluster random sampling technique and consisted of 268 students. They divided into three groups. They were 92 students in the group of first experiment, 88 students in the group of second experiment, and 88 students in the group of third experiment. The instruments to collect the data were test of learning achievement and the questionnaire of learning creativity in mathematics. The data were examined by using two-way ANOVA with unbalanced cells. The results of the research were as follows. (1) Student in the model of PBL model result in a better learning achievement than NHT and TPS learning models. Student in NHT learning model results in a better learning achievement than TPS learning model. (2) Learning creativity gives students a different effect on mathematicsâ learning achievement in the subject of set. The students with the high creativity have a better learning achievement than those with the middle and low categories, and student with the middle creativity have a better learning achievement than those with the low creativity categoriy. (3) In each learning model, students with the high creativity category have learning achievement as good as those with the middle or low categories. (4) In each of the creativity categories of students, students with the high creativity category of PBL have learning achievement as good as those in NHT and TPS, students with the middle creativity category of PBL have better learning achievement than those in TPS, then learning models of NHT and TPS have same learning achievement, and students in PBL and NHT have same learning achievement; last, in the low learning category, student in PBL have better learning achievement than those in TPS, student in NHT and TPS have same learning achievement and the student in PBL and NHT have same learning achievement.Keywords: Â Â  Problem Based Learning, Numbered Head Together, Think Pair Share, and learning creativity.